Effect of low-concentration stressors on the senescence of detached barley leaves - Mayer, Mariann; Nyitrai, Péter; Keresztes, Áron (Acta Biologica Szegediensis, 2005)
Effect of low (sub-micromolar) concentrations of some stress-inducing heavy metals like Cd, Pb, Ni, and Ti salts and the herbicide DCMU on the senescence of chloroplasts was investigated in detached leaves of barley. These agents delayed the loss of chlorophylls and photosynthetic activity (14CO2 fixation). Decrease of the number and size of plastoglobuli in treated chloroplasts also indicated the anti-senescence effect of low-concentration stressors. The active cytokinin content of barley leaves tested by Amaranthus betacyanin bioassay did not show any changes. It is assumed that these stressors may activate a cytokinin-independent signal transduction pathway in the cells.